2017
DOI: 10.18632/oncotarget.16294
|View full text |Cite
|
Sign up to set email alerts
|

IKK inhibition by BMS-345541 suppresses breast tumorigenesis and metastases by targeting GD2+ cancer stem cells

Abstract: We have identified that the ganglioside GD2 is a marker for breast cancer stem cells (BCSCs), and that targeting the enzyme GD3 synthase (GD3S, which regulates GD2 biosynthesis) reduces breast tumorigenesis. The pathways regulating GD2 expression, and their anomalous functions in BCSC, are unclear. Proteomic analysis of GD2+ and GD2- cells from breast cancer cell lines revealed the activation of NFκB signaling in GD2+ cells. Dose- and time-dependent suppression of NFκB signaling by the small molecule inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…We interrogated CMap utilizing the gene expression signatures from SHH MB samples with high and low mRNAsi levels. The CMap analysis precisely identified some compounds that have been shown to specifically impact CSCs in other tumor types (Angeletti et al, 2016;Batsaikhan et al, 2014;Battula et al, 2017;Bonuccelli et al, 2017;Bozok Cetintas et al, 2016;Chen et al, 2015Chen et al, , 2016Cheng et al, 2017;Dominguez-Gomez et al, 2018;Garulli et al, 2014;Hong et al, 2011;Hou et al, 2018;Malkomes et al, 2016;Xiang et al, 2017;Xu et al, 2016;Yeh et al, 2013;Yin et al, 2018;You et al, 2009;Zhang et al, 2013;Zheng et al, 2013a,b). These compounds include the CDK inhibitors palbociclib and alvocidib, the AMPK inhibitor dorsomorphin, the IKK inhibitor BMS-345541, the smoothened receptor antagonist cyclopamine, the topoisomerase inhibitors topotecan and doxorubicin, the GABA receptor agonist ivermectin, the NF-jB pathway inhibitor auranofin, the MTOR inhibitor dactolisib, the AKT inhibitors MK-2206 and pyrvinium-pamoate, the HMGCR inhibitor simvastatin, the HDAC inhibitors apicidin, vorinostat, and givinostat, and the DNA synthesis inhibitor anisomycin.…”
Section: Correlation Of the Immune Cells With Mdnasimentioning
confidence: 99%
“…We interrogated CMap utilizing the gene expression signatures from SHH MB samples with high and low mRNAsi levels. The CMap analysis precisely identified some compounds that have been shown to specifically impact CSCs in other tumor types (Angeletti et al, 2016;Batsaikhan et al, 2014;Battula et al, 2017;Bonuccelli et al, 2017;Bozok Cetintas et al, 2016;Chen et al, 2015Chen et al, , 2016Cheng et al, 2017;Dominguez-Gomez et al, 2018;Garulli et al, 2014;Hong et al, 2011;Hou et al, 2018;Malkomes et al, 2016;Xiang et al, 2017;Xu et al, 2016;Yeh et al, 2013;Yin et al, 2018;You et al, 2009;Zhang et al, 2013;Zheng et al, 2013a,b). These compounds include the CDK inhibitors palbociclib and alvocidib, the AMPK inhibitor dorsomorphin, the IKK inhibitor BMS-345541, the smoothened receptor antagonist cyclopamine, the topoisomerase inhibitors topotecan and doxorubicin, the GABA receptor agonist ivermectin, the NF-jB pathway inhibitor auranofin, the MTOR inhibitor dactolisib, the AKT inhibitors MK-2206 and pyrvinium-pamoate, the HMGCR inhibitor simvastatin, the HDAC inhibitors apicidin, vorinostat, and givinostat, and the DNA synthesis inhibitor anisomycin.…”
Section: Correlation Of the Immune Cells With Mdnasimentioning
confidence: 99%
“…It was reported that BMS-345541 is a potential therapeutic agent for restraining breast tumorigenesis and metastasis through targeting of CSCs. 117 Recent studies have also suggested that BMS-345541 potently inhibits stemness and self-renewal of lung CSCs. In addition, the expression of EMT-related genes and apoptosis resistance were significantly decreased in response to treatment, indicating that NF-κB inhibition is sufficient to both induce apoptosis and prevent EMT in lung CSCs.…”
Section: Bms-345541mentioning
confidence: 99%
“…Alternatively, the non-canonical pathway phosphorylates IkB with an IKKß independent IKKα homodimer resulting in nuclear translocation of RelB. Using antibody array technology, we recently found that the protein p65 (RelA) is highly activated in the GD2 + BCSCs compared to the GD2 − in TNBC cell lines [ 4 ]. Knocking down IKKα, the regulator of both the canonical and non-canonical pathways, inhibited GD3S expression.…”
mentioning
confidence: 99%
“…Knocking down IKKα, the regulator of both the canonical and non-canonical pathways, inhibited GD3S expression. More importantly, it also reduced the percentage of GD2 + BCSCs [ 4 ] suggesting that NFkB signaling regulates BCSC growth in TNBC cells. Next, we tested several small molecule inhibitors targeting NFkB signaling at different stages and identified that BMS345541 (Inhibitor of IKKβ at IC50 0.4μM and IKKα at IC50 4μM) inhibits GD2 and GD3S expression in TNBC cells [ 4 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation